1992
DOI: 10.1093/infdis/165.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Herpes Zoster in the Immunocompromised Host: A Comparative Trial of Acyclovir and Vidarabine

Abstract: Seventy-three immunocompromised patients with disseminated herpes zoster were evaluated in a double-blind controlled trial of acyclovir (n = 37) versus vidarabine (n = 36) therapy. Acyclovir was administered at 30 mg/kg/day at 8-h intervals and vidarabine was given as a continuous 12-h infusion at 10 mg/kg/day for 7 days (longer if resolution of cutaneous or visceral disease was incomplete). No demographic differences existed between treatment groups. No deaths attributable to varicella-zoster virus infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Ara-A has been used for the treatment of herpesvirus infections, but it is less efficient and more toxic than acyclovir [129][130][131][132]. However, ara-A is capable of inhibiting acyclovir-resistant HSV and VZV (varicella-zoster virus) [133][134][135].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Ara-A has been used for the treatment of herpesvirus infections, but it is less efficient and more toxic than acyclovir [129][130][131][132]. However, ara-A is capable of inhibiting acyclovir-resistant HSV and VZV (varicella-zoster virus) [133][134][135].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Morbidity, including pain, scarring, post-herpetic neuralgia, and secondary infection occur in up to one third of patients with VZV infection, and hospitalization may be required with disseminated disease. 1,[7][8][9] VZV disease can occasionally also be fatal after allogeneic HCT, even if treated with acyclovir, with most fatalities occurring during the first year after transplantation. [1][2][3] Furthermore, hepatic or gastrointestinal VZV disease may occur with few or no skin lesions, which often delays the diagnosis and leads to a high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment with antiviral agents, such as ACV and vidarabine, needs to shorten the skin lesions and complications related to herpes zoster. 13 In clinical practice, the start of administration of VACV limited within the first 72 h after the onset of symptoms. These results indicated that CP-44161 could be given over 72 h after the onset; that is, the recalcitrant cases against ACV.…”
Section: Discussionmentioning
confidence: 99%